Gateway to Asia with AeU Online MBA - Borneo, Post (Borneo Post, 2018)
With the world looking to Asia for growth, Asia e University (AeU), a leading open distance learning (ODL) institution situated at the heart of Asia, is the ideal place to gain knowledge on doing business in the region.